The Flow-Induced Degradation and Vascular Cellular Response Study of Magnesium-Based Materials - Shang, Tengda; Wang, Kebing; Tang, Shusheng; Shen, Yang; Zhou, Lei; Zhang, Lu; Zhao, Yuancong; Li, Xin; Cai, Lin; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium (Mg)-based materials are considered as potential materials for biodegradable vascular stents, and some Mg-based stents have obtained regulatory approval. However, the development and application of Mg-based stents are still restricted by the rapid degradation rate of Mg and its alloys. In order to screen out desirable Mg-based materials for stents, the degradation behavior still needs further systematic study, especially the degradation behavior under the action of near-physiological fluid. Currently, the commonly used Mg-based vascular stent materials include pure Mg, AZ31 and WE43. In this study, we systematically evaluated their corrosion behaviors in dynamic environment and studied the effect of their degradation products on the behavior of vascular cells. The results revealed that the corrosion rate of different Mg-based materials was related to the composition of the elements. And the dynamic environment accelerated the corrosion of Mg-based materials. All the same, AZ31 still shows good corrosion resistance. The effect of corrosion products on vascular cells was beneficial to reendothelialization and inhibition of smooth muscle cell proliferation at the implantation site of vascular stent materials.